The Methodological Importance of Applying Speed and Endurance Exercises in Strengthening the Physical Qualities of Athletes - Alimboeva Roziya Davulboevna (European Science Publishing, 2023)
This article delves into the methodological importance of incorporating speed and endurance exercises in the training regimens of athletes. By exploring relevant literature, analyzing established methods, presenting results, and engaging in a comprehensive discussion, this piece aims to provide insights into the multifaceted benefits of integrating these exercises for enhancing overall physical qualities in athletes.
Keywords: Speed training, endurance exercises, athletic performance, strength conditioning, methodology, training protocols, sports science.